Advances in tuna aquaculture : from hatchery to market - Benetti, Daniel; Partridge, Gavin; Buentello, Alejandro; ScienceDirect eBooks (Oxford : Academic Press is an imprint of Elsevier, 2015)
"Advances in Tuna Aquaculture: From Hatchery to Market "provides detailed overviews on the current status of tuna fisheries, fattening, and farming practices, as well as advances in closed-cycle tuna aquaculture. Contributors are renownrenowned scientists, internationally recognized as authorities in their fields. This book addresses all basic and applied aspects of tuna aquaculture, presenting and discussing the global status of tuna fisheries, reproduction, broodstock management, spawning, larval rearing and early developmental stages including nursery and grow out methods. It presents incorporates the most comprehensive and updated data, statistics, and trends in tuna fisheries and aquaculture, covering and addresses a variety of topics ranging fromfrom endocrinology, nutrition, diseases, and genetics to economics and markets. It covers describes recent up-to-date progress on tuna aquaculture and hatchery development. It also provides a synopsisn overview of the challenges presently confronted by tuna aquaculturists, facing tuna aquaculture and and offers innovative views on the challengesbottle-neck issues faced by the industry with the current shift from fisheries to fattening to closed-cycle aquaculture. This is the first book to encompass all aspects related to the tuna aquaculture industry, and merges them into a state-of-the-art compendium that will serve as seminal reference for students, researchers, and professionals working with tuna biology, fisheries, and aquaculture worldwide. Incorporates and reviews the most recent information on tuna fisheries and aquaculturePresents the most innovative production technologies in tuna aquaculture, from hatchery to marketIncludes important information on tuna, derived from industry experience and academic research on larval rearing technology and grow out operations Encompasses and discusses key topics such as genetics, diseases, nutrition, endocrinology, and reproduction, as well as developments, challenges, and future opportunities in tuna aquacultureProvides the latest scientific methods and technologies to maximize efficiencies and productionPresents the independent and collective assessments, viewpoints, and visions of various scientists, all internationally recognized as authorities in the field.
5.2.5 Genetic Analysis of Adult YFT5.2.6 Visual Development of Juvenile and Adult YFT and Considerations for Aquaculture; 5.3 Laboratory Studies of YFT Larvae; 5.3.1 Development, Survival and Growth Dynamics of Larvae; 5.3.1.1 Yolksac Stage; 5.3.1.2 Survival Patterns; 5.3.1.3 Effects of Food Type and Abundance on Larval Growth; 5.3.1.4 Density-Dependent Growth; 5.3.2 Effects of Physical Factors on Survival and Growth; 5.3.2.1 Effects of Water Temperature and Dissolved Oxygen; 5.3.2.2 Effects of Micro-Turbulence on Survival and Growth.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Tuna; Tuna fisheries; NATURE -- Animals -- Fish; SCIENCE -- Life Sciences -- Zoology -- Ichthyology & Herpetology; Thon; Aquaculture; Ressources halieutiques; Tuna; Tuna fisheries; Electronic books